Framing Pacaran sebagai Anugerah: Analisis Nilai Edukatif pada Konten Tiktok Remaja Muslim - Syakhiya Nur Jazilah; Nasrulloh (Al-Kindi, 2026)
The development of social media, particularly TikTok, has opened up new spaces for Muslim teenagers to express their identity and religious experiences in the digital public sphere. One notable phenomenon is the emergence of dating content framed as a “gift” through narratives of gratitude and religious symbols. This study aims to analyze how Muslim teenagers on TikTok frame dating relationships as a blessing, the religious rhetorical strategies used to build self-legitimacy, and the role of the audience in strengthening collective justification. This study uses a qualitative approach with content analysis and framing analysis of five TikTok content selected purposively. Data in the form of videos, captions, and audience comments were analyzed using framing, semiotics, and rhetoric techniques. The results show that dating is framed as a source of happiness, emotional support, and practical benefits that are worthy of gratitude, thus shifting the meaning of gratitude from normative obedience to personal emotional satisfaction. Expressions of gratitude function as symbolic legitimization of dating practices, while audience interactions through prayers and religious affirmations collectively reinforce the normalization of this meaning. These findings indicate the dynamics of digital religiosity among Muslim youth, characterized by the blurring of boundaries between sacred values and profane practices on social media.